2021
DOI: 10.1002/cey2.152
|View full text |Cite
|
Sign up to set email alerts
|

Electrocatalytic and stoichiometric reactivity of 2D layered siloxene for high‐energy‐dense lithium–sulfur batteries

Abstract: Lithium-sulfur batteries (LSBs) have emerged as promising power sources for high-performance devices such as electric vehicles. However, the poor energy density of LSBs owing to polysulfide shuttling and passivation has limited their further market penetration. To mitigate this challenge, two-dimensional (2D) siloxene (2DSi), a Si-based analog of graphene, is utilized as an additive for sulfur cathodes. The 2DSi is fabricated on a large scale by simple solvent extraction of calcium disilicide to form a thin-la… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 47 publications
(52 reference statements)
1
7
0
Order By: Relevance
“…The morphologic optimization is regarded as a promising remedy to expose abundant edge sites and thus ameliorate electrocatalytic activity of heterogeneous nanocatalyst. [ 47–51 ] However, their electrocatalytic activity is in essence restricted by the intrinsic electronic structure. In further context, the pristine nanocatalyst can scarcely execute bidirectional redox reactions due to their single active site.…”
Section: Introductionmentioning
confidence: 99%
“…The morphologic optimization is regarded as a promising remedy to expose abundant edge sites and thus ameliorate electrocatalytic activity of heterogeneous nanocatalyst. [ 47–51 ] However, their electrocatalytic activity is in essence restricted by the intrinsic electronic structure. In further context, the pristine nanocatalyst can scarcely execute bidirectional redox reactions due to their single active site.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] Since the concept of catalyst was introduced into the lithium-sulfur system, it has been expected to solve the above problems. [7][8][9][10] Recently, lots of efforts have been made to explore excellent cathode materials, such as metal oxides, [11][12][13] sulfides, [14][15][16] nitrides, [17][18][19] and carbides. [20][21][22] Nonetheless, the poor conductivities of the aforementioned polar materials make them need to be combined with abundant carbon materials to speed up the reaction kinetics, 23,24 which in turn brings other problems such as low sulfur content and low volume capacity.…”
Section: Introductionmentioning
confidence: 99%
“…To date, considerable efforts have been made toward optimization of sulfur and lithium evolution behaviors from various perspectives 8,9 . Accordingly, some favorable progress has been achieved by utilizing various hosts with tailored morphologies, controllable structures, and rich surface chemistries to alleviate the LiPS shuttle effect and propel sulfur redox kinetics 10,11 . Previous studies have demonstrated that the study of sulfur reaction kinetics is the key to breaking through the gap between academic investigations and actual implementation of LSBs.…”
Section: Introductionmentioning
confidence: 99%